Peran strategis public relation dalam membangun citra dan kepercayaan publik terhadap perbankan syariah - Nurwulandari, Alfina Dwi (Maliki Interdisciplinary Journal, 2025)
The Islamic banking industry in Indonesia is experiencing rapid growth, but still faces challenges in building its image and public trust. Public relations (PR) plays a strategic role as a communication bridge between banks and the public, utilizing both conventional and digital media. This research uses a descriptive-qualitative approach based on literature review from several recent journals. The analysis shows that PR can build a positive image through Islamic financial education, transparent communication, and the implementation of corporate social responsibility (CSR) programs. Furthermore, digital public relations innovations help strengthen the reputation of Islamic banks in the era of digital transformation by reaching a wider audience. Effective PR also contributes to increased customer loyalty and trust through responsive and ethical crisis communication management. Therefore, an integrative and adaptive PR strategy is a crucial element in strengthening public trust in Islamic banking in Indonesia.